¿Cómo El Viento Afecta Las Casas? - Kathleen C. Ruppert; Hal S. Knowles, III; Karla A. Lenfesty (EDIS)
This is part of the Education + Action = Wind Damage Mitigation series by Kathleen C. Ruppert, Hal S. Knowles, and Karla A. Lenfesty that is now available in Spanish and Haitian Creole